Strategic Leadership in Digital Transformation: Organizational Capabilities and Performance Outcomes - Hadi, Mokhamad Yaurizqika (PT. Riset Press International, 2025)
Digital transformation has emerged as a critical imperative for organizations seeking to maintain competitive advantage in an increasingly digital economy. This study examines the role of strategic leadership in driving successful digital transformation initiatives and their impact on organizational capabilities and performance outcomes. Through a comprehensive analysis of existing literature and theoretical frameworks, this research explores how strategic leaders navigate the complexities of digital transformation, develop necessary organizational capabilities, and achieve superior performance outcomes. The study reveals that strategic leadership plays a pivotal role in orchestrating digital transformation through vision articulation, resource allocation, culture transformation, and capability building. Organizations with effective strategic leadership in digital transformation demonstrate enhanced innovation capabilities, improved operational efficiency, better customer engagement, and superior financial performance. The findings suggest that strategic leaders must adopt a holistic approach that integrates technological advancement with organizational change management, talent development, and cultural transformation. This research contributes to the growing body of knowledge on digital transformation leadership and provides practical insights for executives leading digital initiatives in their organizations.